Analisis Kontrukstif Ketidakberdosaan Yesus dalam Menjalankan Misinya di Dunia - Sarma Marpaung; Yusup Rogo Yuono (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2024)
The humanity and sinlessness of Jesus Christ in carrying out His mission in the world, has always been an interesting theme and invites debate, both among theologians and secularists. Human weakness in understanding and accepting the fact of the dual nature of Jesus Christ, presents various skeptical views, rejections and refutations, including suspicion and doubt that in carrying out His mission, Jesus did not act in His sinless human nature, but in His holy divine nature. However, whatever the forms of rejection, suspicion and debate against that view, the truth of God's Word is accurate evidence and at the same time an answer. This study aims to test the truth that during His mission in the world, Jesus was a true sinless human being, using a method using a qualitative approach using secondary techniques through literature studies.The humanity and sinlessness of Jesus Christ in carrying out His mission in the world has always been an interesting theme and has invited debate, both among theologians and secularists. Human weakness in understanding and accepting the fact of the dual nature of Jesus Christ, presents various views of skepticism, rejection and refutation, not least the suspicion and doubt that in carrying out His mission, Jesus did not act in His sinless human nature, but in His holy divine nature. However, whatever the forms of rejection, suspicion and debate regarding this view, the truth of God's Word is accurate evidence and at the same time the answer that Jesus' human nature is real and during the mission of His redemptive work Jesus acted with His sinless human nature. The results of the study concluded that Jesus' humanity was real, and during his redemptive mission, Jesus acted with a sinless humanity. This study confirms that even though Jesus experienced a full human life, including suffering and weakness, He still lived without sin and without moral fault. This is an important belief in Christian theology that emphasizes that Jesus' humanity does not diminish His purity and holiness in carrying out his redemptive mission for humanity.